1253. Acceptability and feasibility of long-acting injectable antiretroviral therapy for persons who inject drugs in Vietnam: using the Consolidated Framework on Implementation Research to identify determinants and inform implementation strategies. (15th December 2022) - Rutstein, Sarah E; Sibley, Adams L; Nguyen, Trang Thu Do; Tran, Ha Viet; Giang, Le Minh; Sripaipan, Teerada; Nguyen, Minh; Huffstetler, Hanna E; Miller, William C; Eron, Joseph J; Gay, Cynthia L; Go, Vivian F
Abstract: Background: Long-acting injectable antiretroviral therapy (LAI) is an exciting alternative to daily oral ART. Less frequent dosing afforded by LAI may be especially pertinent for persons who inject drugs (PWID), who experience more HIV-related mortality largely driven by inadequate ART adherence. We used the Consolidated Framework on Implementation Research (CFIR) to characterize determinants of LAI implementation, focusing on use among PWID, in Hanoi, Vietnam. Methods: We conducted in-depth interviews with HIV-infected PWID, ART providers, and policymakers using purposive sampling, recruiting respondents with diverse ART experience from public HIV/ART clinics and national regulatory agencies. Participants were briefed regarding LAI ART, including administration, effectiveness, side effects, and dosing frequency. Data were coded and analyzed using thematic analysis. Results: We interviewed 19 PWID, 14 providers, and five policymakers (February-November, 2021). We identified recurrent themes in CFIR domains. Intervention : All informants were excited about LAI, citing convenience and discrete dosing as major facilitators. Surprisingly, provider concerns, including more frequent clinic visits and injection reactions, were rarely voiced by PWID who described monthly injections as similar to current visit frequency and cited "high pain tolerance." Outer : Providers and policymakers were eager to offer patients ART choice but were divided as to if LAI distribution should proceed with sub-population prioritization. Inner : Providers described personnel and clinic logistic concerns but were confident these could be addressed. Individual : Providers were motivated and confident in their ability to deliver LAI. Process : Transitions to new ART and provision of COVID-19 vaccines were frequently invoked by providers and policymakers as interventions informing LAI implementation. Figure Determinants of LAI ART implementation in Vietnam using the domains of the Consolidated Framework on Implementation Research Conclusion: Using CFIR, we identified multiple determinants of LAI implementation in Vietnam. Stakeholders agreed that LAI was feasible and acceptable. Medication tolerance and efficacy concerns highlight the importance of patient and provider education. Areas where stakeholders diverge should be considered in designing LAI implementation strategies. Disclosures: Joseph J. Eron, MD, Adagio Therapeutics: data safety monitoring committee|Gilead Sciences: Advisor/Consultant|Gilead Sciences: Grant/Research Support|Glaxo Smith Kline: Advisor/Consultant|Merck: Advisor/Consultant|ViiV Healthcare: Advisor/Consultant|ViiV Healthcare: Grant/Research Support.